PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PT BPR KARTASURA SARIBUMI CABANG MASARAN - Juni Trisnowati (JURNAL EKONOMI BISNIS DAN KEWIRAUSAHAAN, 2013)
This study analyzesthe influence ofmotivationand disciplineto theperformance of employeesof PTBPRKartasuraSaribumiCabang Masaran. The problemsareformulatedis:is there asignificant relationship betweenmotivationand disciplineto employee performanceeither partially orsimultaneously. The hypothesis is"suspected ofmotivationand disciplinehas a significant influenceon the performance ofemployees ofPTBPRKartasuraSaribumiCabangMasaraneither partially orsimultaneously". Datacollectedprimary dataobtainedthrough a questionnairegiven tothe respondent, and thenumber ofrespondentsas many as 14employees.The analysisincludes thecoefficientof determination, multiple linearregressionanalysis, t testand F test.Results showedthat theproposed hypothesisaccepted as true, which means thatthere is asignificant influenceeither partially orsimultaneouslybetweenmotivationand disciplineto the performance ofemployees of PTBPRKartasuraSaribumiCabang Masaran.